I hate everything a book about feeling angry - Graves, Sue; Guicciardini, Desideria (London Franklin watts, 2015)
Sam is having a bad day and nothing is going right. Dad is too busy to play with him, he doesn't like his lunch and he doesn't enjoy Archie's party. Can Aunt Jen help him to stop feeling so angry
Education
Keywords: Educational psychology